REPRESENTASI PESAN DAKWAH MELALUI KARTUN DI AKUN INSTAGRAM @hijabalila - Laili, Filna; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Â Phenomenon of social media Instagram as a medium for disseminating information, has a great response as the target recipient of information. A variety of information disseminated by social media Instagram, one of which is the message of da'wah. The message of da'wah spread by the hijab alila instagram account is through the promotion and dissemination of information about da'wah in the form of cartoon illustrations. Alila's hijab account uses representationsthe inform of cartoon images as da'wah content on her Instagram. One cartoon image can represent thousands of meanings received by the reader. The purpose of this study was to determine the meaning of denotation, connotation and myth representation of da'wah messages through cartoons on the hijab alila instagram account. By using the theory of Roland Barthes' Semiotics Analysis and obtained the meaning contained in the propaganda cartoon image. The research method used by the researcher is a qualitative research method with a descriptive approach. To analyze the data, the researcher used Roland Barthes Semiotic Analysis by examining 5 units of analysis. In the two-stage signification idea model (two orders of signification), namely denotation and connotation. The connotation is identical to the ideological operation which is known as myth. Analyzing each unit of analysis, namely propaganda cartoon images from February, July, and September 2020. The images are propaganda cartoon images that have the likes most. Data collection techniques in this study were research techniques, interviews and documentation. The results of this study based on Roland Barthes' Semiotics analysis on the illustration of the hijabalila Islamic da'wah cartoon image showing three components of meaning. First, the meaning of denotation in making the da'wah cartoon, the illustrator team draws according to the provisions without violating the rules of law in Islam. Second, the connotations are described using design an attractivewith a selection of colors, fonts,illustrations and themes more hits and has a message that can be a concern in thecommunity.And thirdly, the meaning of myth is to give a da'wah message that has a positive response effect, in this case followers activecan see the truth of the message conveyed in accordance with the Qur'an and Hadith.